2018
DOI: 10.1021/acs.joc.7b03216
|View full text |Cite
|
Sign up to set email alerts
|

Hemisynthesis of 2,3,4-13C3-1,4-Androstadien-3,17-dione: A Key Precursor for the Synthesis of 13C3-Androstanes and 13C3-Estranes

Abstract: In this contribution, we describe two simple and efficient routes for the preparation of keto-aldehyde 1, a key intermediate for the synthesis of C3-androstanes andC3-estranes. In the first route, the targeted aldehyde 1 was obtained in 40% overall yield from 1,4-androstadien-3,17-dione (3 mmol scale) via a two-step sequence involving a one-pot, abnormal ozonolysis/sulfur oxidation/retro-Michael/ozonolysis process. Alternatively, a second route from 4-androsten-3,17-dione, using a six-step sequence, was optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 63 publications
1
11
1
Order By: Relevance
“…An excess of MeI was added to a part of the resulting solution to convert PPh 3 into (MePPh 3 )I. 64 After stirring for 1 h, all volatiles were removed under reduced pressure. The residue, containing (MePPh 3 -d 0 )I, (MePPh 3 -d 5 )I, (MePPh 3 -d 10 )I, and (MePPh 3 -d 15 )I, was dissolved in MeOH and analyzed massspectrometrically.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An excess of MeI was added to a part of the resulting solution to convert PPh 3 into (MePPh 3 )I. 64 After stirring for 1 h, all volatiles were removed under reduced pressure. The residue, containing (MePPh 3 -d 0 )I, (MePPh 3 -d 5 )I, (MePPh 3 -d 10 )I, and (MePPh 3 -d 15 )I, was dissolved in MeOH and analyzed massspectrometrically.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, the mixture was filtered over alumina to remove the metal complex, and an excess of CH 3 I was added to a part of the resulting solution to convert PPh 3 into the corresponding phosphonium salt (CH 3 PPh 3 )I. 64 After stirring for 1 h, all volatiles were removed under reduced pressure. The residue, containing (CH 3 PPh 3 -d 0 )I, (CH 3 PPh 3 -d 5 )I, (CH 3 PPh 3 -d 10 )I, and (CH 3 PPh 3 -d 15 )I, was dissolved in methanol and analyzed mass spectrometrically.…”
Section: Reactivity In Solutionbenzene Eliminationmentioning
confidence: 99%
“…The latter was then reduced by treatment with NaBH 4 to the expected 2-oxa-3-oxo-Δ 4 In view of our long-standing interest in the synthesis of stable isotope labeled compounds, 63 we embarked on the development of an efficient, large-scale synthesis that would ensure the incorporation of 13 C atoms into the steroid framework. 64 From a strategic point of view, we were very interested in the approach previously reported by Vierhapper and co-workers, 53 which allowed for the latestage reconstruction of the A ring with a labeled Wittig reagent 85 ([ 13 C 3 ]-1-(triphenylphosphoranylidene)propan-2one) from a 10-formyl-5-oxo-des-A intermediate 99 (see Scheme 16). At this point, several questions remained to be answered.…”
Section: Scheme 19 Total Synthesis Of Testosterone Via a Key 10-formymentioning
confidence: 99%
“…First, we focused our attention on the double oxidative cleavage of the two C=C bonds in the A ring of 98 in order to access rapidly the desired ketoaldehyde 99. 64 Unfortunately, after extensive attempts we found that the A ring of 98 was either inert under standard ozonolysis conditions or led to decomposition under oxidative cleavage conditions with potassium permanganate (Scheme 22). At this point, we reasoned that disruption of the electronic conjugation of the dienone system in the A ring in 98 by a regioselective reduction of the carbonyl at C3 could be a solution to elabo-rate our previous plan.…”
Section: Scheme 21 Synthetic Plan For the Preparation Of [234-13 C mentioning
confidence: 99%
See 1 more Smart Citation